Original Solution for Middle Ear Implant and Anesthetic/Surgical Management in a Child with Severe Craniofacial Dysmorphism - Giovanni Bianchin; Lorenzo Tribi; Aronne Reverzani; Patrizia Formigoni; Valeria Polizzi (Case Reports in Otolaryngology)
We describe the novel solution adopted in positioning middle ear implant in a child with bilateral congenital aural atresia and craniofacial dysmorphism that have posed a significant challenge for the safe and correct management of deafness. A five-year-old child, affected by a rare congenital disease (Van Maldergem Syndrome), suffered from conductive hearing loss. Conventional skin-drive bone-conduction device, attached with a steel spring headband, has been applied but auditory restoration was not optimal. The decision made was to position Vibrant Soundbridge, a middle ear implant, with an original surgical application due to hypoplasia of the tympanic cavity. Intubation procedure was complicated due to child craniofacial deformities. Postoperative hearing rehabilitation involved a multidisciplinary team, showing improved social skills and language development.